Multi-joint vs single-joint resistance exercises induce a similar strength increase in trained men: A randomized longitudinal crossover study - Brigatto, F. A.; de Camargo, J. B. B.; De Ungaro, W. F.; Germano, M. D.; Marchetti, P. H.; Aoki, M. S.; Braz, T. V.; Lopes, C. R. (International Journal of Exercise Science, 2020)
The type of exercise is a relevant resistance training-variable that might be manipulated in order to induce significant increases in muscle strength. The aim of this study was to analyze the influence of multi-joint vs single-joint resistance exercises on maximal strength. Sixteen resistance-trained men (age: 23.1 ± 4.4 years; body mass: 86.0 ± 12.8; height: 177.9 ± 6.4 cm; training experience: 4.2 ± 3.4 years) performed one of the following training protocols for six weeks: MULTI, consisting of only multi-joint exercises or SINGLE, consisting of only single-joint exercises. Subjects were then submitted to a three-week washout period, before being submitted to the other protocol for another six weeks. A linear periodization model was adopted in which external load was increased and the repetition range was decreased every two weeks. Maximal dynamic strength of bench press (1RMBENCH) and squat exercises (1RMSQUAT), a percentage variation of total load lifted (DeltaTLL) and internal training load (ITL) were measured. Similar increases in 1RMBENCH (MULTI: 10.8%, p < 0.001; SINGLE: 5.5%, p < 0.001) and 1RMSQUAT (MULTI: 19.7%, p < 0.001; SINGLE: 19.0%, p < 0.001) were observed after the MULTI and SINGLE protocols. A decrease in TLL was detected for both exercise protocols; however, the SINGLE protocol induced a greater decrease, compared to the MULTI protocol (-35 ± 11% vs -42 ± 5%, respectively; p = 0.026). A greater ITL for the MULTI was observed when compared to the SINGLE (12.1%; p < 0.001). In conclusion, resistance training protocols with different exercise modalities seem to produce similar strength increases in resistance-trained men.